ANALISA KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PEMBANGUNAN KONSTRUKSI BANDARA SISI DARAT DAN PEMBANGUNAN MALL PENTACITY SHOPPING VENUE BSB - Tito Perdana Putra, Bagoes (KURVA S JURNAL MAHASISWA, 2014)
Based on the problems found, ie How the implementation of Occupational Health and Safety (K3) on the construction of the airport land side development and construction of shopping mall venue pentacity bsb? the purpose of this research is as follows: Knowing the implementation of Occupational Health and Safety (K3) on the construction of the airport land side development and construction of shopping mall pentacity bsb venue.               Occupational safety and health is an approach that determines the standard comprehensive and (specific), the determination of government policy on corporate practices in workplaces and implementation through letters court, fines and other laws .               From the discussion, it is concluded that the very importance of the implementation of Health and Safety (K3) on the construction of the airport land side development and construction of shopping mall pentacity bsb venue. Suggestion of this research is the need for training in the implementation of K3 management so that all responsible parties in the company has sufficient ability and know about manejemen K3.